The Integration of phoenician communities in the Iberian Peninsula during the Roman Empire from a postcolonial perspective - Machuca Prieto, Francisco (My University, 2015)
The goal of this paper is to research on the analysis of the process of integration experienced by the Phoenician-Punic communities of the Iberian Peninsula in the Roman world, from the end of the Second Punic War (206 BCE) until Flavian times (mid-1st Century CE). The main goal is to explain the process of identity construction among these communities and the changes that led to their gradual transformation into Roman ciuitates. This thesis tries to overcome the traditional one-way approaches applied the “Romanization” process in the Ulterior-Baetica province. In this regard, we reinterpret the so-called “Punic cultural resistances” as identitarian reworkings within the Roman world.
Keywords: Fenicios - Península Ibérica; Phoenician; Iberian Peninsula; Roman Empire; Identity; Postcolonialism